2002
DOI: 10.1007/bf02897981
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of secretory Ig A in saliva and its daily variation by academic stress

Abstract: It may be possible to use this measurement to monitor psychological stress in students and workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Secretory Immunoglobulin A (SIgA) is the main immunoglobulin found in salivary glands, which play a key role in protecting from infection vulnerable tissues such as the oral cavity, lungs, and gut [ 59 ]. SIgA in saliva interacts with the autonomic nervous system, changing its concentration in response to physical and psychological stresses [ 60 , 61 , 62 ] and changing the saliva flow rate [ 63 ]. SIgA antibodies are present in saliva and are able to react to a large variety of indigenous bacteria.…”
Section: Salivary Igamentioning
confidence: 99%
“…Secretory Immunoglobulin A (SIgA) is the main immunoglobulin found in salivary glands, which play a key role in protecting from infection vulnerable tissues such as the oral cavity, lungs, and gut [ 59 ]. SIgA in saliva interacts with the autonomic nervous system, changing its concentration in response to physical and psychological stresses [ 60 , 61 , 62 ] and changing the saliva flow rate [ 63 ]. SIgA antibodies are present in saliva and are able to react to a large variety of indigenous bacteria.…”
Section: Salivary Igamentioning
confidence: 99%
“…Several studies repeatedly demonstrated relations between SIgA variations and psychological stress of students (Guo et al, 2002). Levels of SIgA are influenced by additional factors such as amount of water consumption (Backes et al, 2015), physical activity and physical challenge (Cieslak et al, 2003;Dwyer et al, 2010;Gleeson and Pyne, 2000), changes in biorhythms during work shift (Guo et al, 2002;Lac and Chamoux, 2003), time of the season, location, altitude above sea level and most of all by stress related to psychological challenge and persisting physical challenge (Cieslak et al, 2003;Cohen et al, 2001;Gleeson and Pyne, 2000;Guo et al, 2002;Hunter et al, 2011;Kidd et al, 2011;Powell et al, 2015;Yang et al, 2002). Two major branches of stress induction include autonomous nervous system and hypothalamus-adrenal gland-pituitary axis.…”
Section: Introductionmentioning
confidence: 98%